Finding evidence for treatment decisions in a pandemic. Issue 7 (July 2022) - Paneth, Nigel; Joyner, Michael J.; Casadevall, Arturo
Abstract : The randomized controlled trial (RCT) is the mainstay of treatment evidence in medicine because it is the most rigorously conducted and analyzed form of human research. Yet, the intense and detailed methodology that has evolved to implement RCTs has reduced their value in providing timely and useful evidence of the effectiveness of medical or public health interventions in pandemic conditions. The crisis conditions of a pandemic illustrate the need for medicine to take a broader view of the evidentiary landscape to include evidence from sources other than conventional RCTs. Such sources include analyses of vital data, observational research, quasi-experiments, and flexible RCTs carefully designed to address underlying biological and clinical realities and to avoid unnecessary rigidity. Highlights: During pandemics, health care and public health professionals rarely have all the information required for decision-making. Randomized trials are the key source of regulatory decisions and clinical recommendations, but they can be misleading, especially when conducted under pandemic conditions. Problems include the high likelihood of false-negative trials, lack of generalizability, and trial interruptions because of pandemic waning of cases. Some authors have recommended that more attention be paid in decision-making to 'real-world evidence', including vital data, propensity-matched cohort studies, some forms of administrative data, and quasi-experiments. In addition, trials can be improved by taking a fuller account of the pathophysiology of the condition under investigation and its relation to the agent studied. More use can be made of adaptive trials that can flexibly be modified to changing circumstances. Pandemic conditions reveal the need to broaden the evidentiary base beyond the conventional randomized trial.